The Glyptothorax of the Bolaven Plateau, Laos (Teleostei: Sisoridae): new and endangered - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2017)
Glyptothorax forabilis, new species, and G. porrectus, new species, are described from the Bolaven Plateau in southern Laos. Both species closely resemble G. laosensis, but can be distinguished from it and other Indochinese congeners by combinations of color pattern, morphometry (with particular regards to the eye, body depth, and caudal peduncle) and thoracic adhesive apparatus morphology. Both species are endemic to the Bolaven Plateau, have a very limited distribution and are threatened by hydropower and agricultural activities.